História da ciência em sala de aula: uma proposta para a abordagem do desenvolvimento dos conceitos de peso do ar e pressão atmosférica - Silva, Dayson de Mello (2016)
The present work proposes the use of science history in the classroom as a tool facilitating the construction of knowledge by students. We comment on the current situation of Physics teaching and then we move to the importance of a physics education contextualized in its history. The work also makes a link between the use of science history with the theory of meaningful learning of Ausubel. For the application of this historical methodology, an educational product was created, that consists in an apostille containing the historical period related to the establishment of the air weight and atmospheric pressure. The apostille provides historical material concerning the transition from Aristotelian thought the horror of emptiness in favor of a theory founded on experiments and measurement process. To that end, it made the monitoring of contributions from four major scientists: Evangelista Torricelli, Blaise Pascal, Otto von Guericke and Robert Boyle. The historical material was applied to the students in the classroom by making use of slides, videos and an application that simulates the dependence of the pressure and volume occupied by a gas. All this content is available on a blog, created to facilitate access to the generated product. The results of the methodology applied were quite satisfactory, and the vast majority of students obtained a considerable growth.